2019
DOI: 10.3390/pr7090568
|View full text |Cite
|
Sign up to set email alerts
|

Raw Material Variability and Its Impact on the Online Adaptive Control of Cohesive Powder Blend Homogeneity Using NIR Spectroscopy

Abstract: It is significant to analyze the blend homogeneity of cohesive powders during pharmaceutical manufacturing in order to provide the exact content of the active pharmaceutical ingredient (API) for each individual dose unit. In this paper, an online monitoring platform using an MEMS near infrared (NIR) sensor was designed to control the bin blending process of cohesive powders. The state of blend homogeneity was detected by an adaptive algorithm, which was calibration free. The online control procedures and algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…To effectively detect the CQAs and gain a deeper understanding of the change in dynamics of the mixing process, near-infrared (NIR) instruments are widely used PAT tools to monitor the blending process. 47,146–151 The application of Raman spectroscopy in a study of the mixing process has also been reported. 152–154 However, in order to obtain meaningful results, spectral data must be transformed by chemometrics.…”
Section: Application Of Multivariate Modeling Techniques In Tablet Ma...mentioning
confidence: 99%
See 1 more Smart Citation
“…To effectively detect the CQAs and gain a deeper understanding of the change in dynamics of the mixing process, near-infrared (NIR) instruments are widely used PAT tools to monitor the blending process. 47,146–151 The application of Raman spectroscopy in a study of the mixing process has also been reported. 152–154 However, in order to obtain meaningful results, spectral data must be transformed by chemometrics.…”
Section: Application Of Multivariate Modeling Techniques In Tablet Ma...mentioning
confidence: 99%
“… 152–154 However, in order to obtain meaningful results, spectral data must be transformed by chemometrics. 47 Multivariate modeling approaches, which play an important role in translating spectral signals to BU, can be applied to monitor the mixing process.…”
Section: Application Of Multivariate Modeling Techniques In Tablet Ma...mentioning
confidence: 99%
“…[16][17][18] NIR spectroscopy can provide accurate measurement in a simple and real-time way, and it has been successfully applied to quality control of Chinese medicine and Chinese herbal preparation manufacturing processes. [19][20][21][22][23] Once the NIR method is developed, methodology validation is a mandatory step at the end of the development to provide guarantees that each of the future results during routine use will be accurate and precise. Conventionally, the performance of the NIR method is evaluated by chemometric parameters.…”
Section: Introductionmentioning
confidence: 99%